2014
DOI: 10.1111/bcp.12373
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant oral and intravenous pharmacokinetics of trametinib, a MEK inhibitor, in subjects with solid tumours

Abstract: AIMSThe aim of this phase 1, single centre, open label study in four patients with solid tumours was to determine the absolute bioavailability of a 2 mg oral dose of trametinib. Trametinib is an orally bioavailable, reversible and selective allosteric inhibitor of MEK1 and MEK2 activation and kinase activity. METHODSA microtracer study approach, in which a 5 μg radiolabelled i.v. microdose of trametinib was given concomitantly with an unlabelled 2 mg oral tablet formulation, was used to recover i.v. and oral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Consistently with this hypothesis, cell viability analysis as a function of treatment with kinase inhibitors showed that CDs+ cases were more sensitive than CDs-to MEKi (at 10, 100 and 1,000nM), FLT3/PKCi (1 and 10μM) and PAKi (1μM) (Figure 1c). These concentrations are physiologically relevant for MEKi and FLT3/PKCi 8,9 .…”
mentioning
confidence: 99%
“…Consistently with this hypothesis, cell viability analysis as a function of treatment with kinase inhibitors showed that CDs+ cases were more sensitive than CDs-to MEKi (at 10, 100 and 1,000nM), FLT3/PKCi (1 and 10μM) and PAKi (1μM) (Figure 1c). These concentrations are physiologically relevant for MEKi and FLT3/PKCi 8,9 .…”
mentioning
confidence: 99%
“…Indeed the determination of F abs in this way is scientifically superior to the conventional two‐period crossover design, where there is a potential for non‐linear kinetics to affect the calculation if circulating drug concentrations are significantly different between the intravenous and extravascular dose routes, and the potential error arising from temporal and/or intra‐individual variability is reduced by determining concentrations arising from both dose routes in a single dose period. A number of recently published papers relating to stand‐alone intravenous microtracer studies illustrate the utility of the approach …”
Section: Clinical Study Designmentioning
confidence: 99%
“…Microtracer studies designed to obtain intravenous PK conducted to date published in the peer‐reviewed literature are summarized in Tables and . Over time, the design of the microtracer study as evolved so that the intravenous dose is administered typically as an infusion to coincide with the t max of the extravascular dose.…”
Section: Literature Summary Of Microtracer Studiesmentioning
confidence: 99%